Back Cover: Fe/Fe3C/N‐Doped Carbon Materials from Metal–Organic Framework Composites as Highly Efficient Oxygen Reduction Reaction Electrocatalysts (ChemPlusChem 8/2016). Issue 8 (19th July 2016) - Qian, Yuhong; Cavanaugh, Jack; Khan, Inayat Ali; Wang, Xuerui; Peng, Yongwu; Hu, Zhigang; Wang, Yuxiang; Zhao, Dan
Abstract : The cover picture shows a metal–organic framework, MIL‐88c‐Fe, which was converted into Fe/Fe3 C/N‐doped porous carbon material having excellent catalytic activity toward oxygen reduction reactions and that is suitable for application in electrochemical energy storage and conversion devices such as fuel cells and metal–air batteries. More details can be found in the Communication by Dan Zhao and co‐workers onpage 857 in Issue 8, 2016 (DOI:10.1002/cplu.201600174 ).